Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/s005310000158
|View full text |Cite
|
Sign up to set email alerts
|

Relating experimental and geological rheology

Abstract: This paper is concerned with the question of how to relate laboratory measurements of the rheology of rocks to the rheological assumptions that need to be made in geodynamic modelling. First, there is a brief resumØ of the principal types of rheological behaviour that have been studied in the laboratory, both pressure-dependent, strain rate-independent and pressure-independent, strain-rate-dependent. Then, the generalization of the results from the relatively simple stress states of the experiments to general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…The strength and deformation behavior of the continental and oceanic crust is generally assumed to depend on observation scale (Paterson, 2001). Localized heterogeneities like fault zones control the development of the brittle upper crust (Ben-Zion and Sammis, 2013;Faulkner et al, 2010), whereas high temperature shear zones impose constraints on the mechanical behavior of the lower ductile crust (Bürgmann and Dresen, 2008;Handy et al, 2007;Platt and Behr, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…The strength and deformation behavior of the continental and oceanic crust is generally assumed to depend on observation scale (Paterson, 2001). Localized heterogeneities like fault zones control the development of the brittle upper crust (Ben-Zion and Sammis, 2013;Faulkner et al, 2010), whereas high temperature shear zones impose constraints on the mechanical behavior of the lower ductile crust (Bürgmann and Dresen, 2008;Handy et al, 2007;Platt and Behr, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of such data is the problem of extrapolation to slow natural strain rate and from laboratory to larger scales (Paterson 1987(Paterson , 2001. In contrast, studies of microstructures in naturally deformed minerals can potentially provide information on the deformation mechanisms that actually operate in the Earth.…”
Section: Deformation Mechanisms and Rheology Of Crust And Upper Mantlmentioning
confidence: 99%
“…The fastest strain rates with such processes (10 -10 s -1 , Gratier et al, 2009) are found within active creeping zones, such as along the San Andreas fault (Titus et al, 2006). Reproducing such low strain rates on natural minerals in the presence of a fluid in the laboratory is therefore a challenge (Paterson, 2001). Strain rates as low as 10 -11 s -1 may be registered in the lab (Gratier, 1993;Dysthe et al, 2003;Berest et al, 2004;Le Guen et al, 2007;Gratier et al, 2009), however the strain values are very low and not necessary representative of large finite deformation.…”
Section: Introductionmentioning
confidence: 99%